Rapid and Low‐Temperature Salt‐Templated Production of 2D Metal Oxide/Oxychloride/Hydroxide. Issue 45 (25th September 2019) - Gu, Jianan; Zhang, Chao; Du, Zhiguo; Yang, Shubin
Abstract: 2D materials have played an important role in electronics, sensors, optics, electrocatalysis, and energy storage. Many methods for the preparation of 2D materials have been explored. It is crucial to develop a high‐yield, rapid, and low‐temperature method to synthesize 2D materials. A general, fast (5 min), and low‐temperature (≈100 °C) salt (CoCl2 ·6H2 O)‐templated method is proposed to prepare series of 2D metal oxides/oxychlorides/hydroxides in large scale, such as MoO3, SnO2, SiO2, BiOCl, Sb4 O5 Cl2, Zn2 Co3 (OH)10 2H2 O, and ZnCo2 O4 . The as‐synthesized 2D materials possess an ultrathin feature (2–7 nm) and large aspect ratios. Additionally, these 2D metal oxides/oxychlorides/hydroxides exhibit good electrochemical properties in energy storage (lithium/sodium‐ion batteries) and electrocatalysis (hydrogen/oxygen evolution reaction). Abstract : A fast and low‐temperature salt‐templated method is proposed to prepare a series of 2D metal oxides/oxychlorides/hydroxides, such as MoO3, SnO2, SiO2, BiOCl, Sb4 O5 Cl2, Zn2 Co3 (OH)10 2H2 O, and ZnCo2 O4 . These 2D materials possess both the ultrathin feature (2–7 nm) and large aspect ratios, and exhibit good electrochemical properties in energy storage (lithium/sodium ion batteries) and electrocatalysis (hydrogen/oxygen evolution reaction).